The Value of CSR in Times of Increased Policy Uncertainty: Evidence from the Brexit Referendum - Olivia Hohlwegler (Junior Management Science (JUMS), 2021)
Scrutinising the 2016 Brexit Referendum, this paper examines the impact of economic policy uncertainty on the relationship between corporate financial performance and CSR using a sample of 320 non-financial firms listed at the London Stock Exchange. The sample covers the period of 2014 to 2018 with 2016 marking increased, and 2017 and 2018 representing years of moderated policy uncertainty. Using cross-sectional regression analysis of shock-period buy-and-hold returns, this paper finds (I) a statistically and economically significant inverse relationship between reservoirs of social capital previously accrued through CSR initiatives and returns. The effect is driven by the Governance component of CSR, whereas the impact of combined Environmental and Social pursues was not found to be meaningful. Using difference-in-difference methodology with continuous treatment, this investigation concludes (II) high-CSR and low-CSR firms do not differ in terms of sensitivity to adverse Brexit shock implications on operating performance, profitability, financial health, and firm value. Further, (III) effects of CSR on aforementioned aspects of real performance were not found to vary alongside levels of policy uncertainty.
Keywords: 650; Brexit referendum; CSR; ESG investing; policy uncertainty